Synthesis and structure-activity studies of skeletally modified estradiol analogues - De Koning, Pieter David (Department of Chemistry, 2017)
In the first phase of this investigation, synthetic approaches to skeletally modified variants of 14,17α-ethanoestra-l,3,5(10)-triene-3,17β-diol were examined, with the purpose of determining the influence of configurational inversion at C-8, C-9 or C-13 upon the high oral estrogenicity associated with introduction of a 14, 17-ethano bridge into the estradiol skeleton. 3-Methoxyestra-1,3,5(10)-trien-17-one was converted conventionally into the 13α-isomer, which underwent sequential silyl enol ether formation and dehydrosilylation into 3-methoxy-13α-estra-1,3,5(10), 15-tetraen-17-one, which failed to undergo conversion into the corresponding 3-methoxy-13α-estra-1,3 ,5( 10), 14, 16-pentaen-17-yl acetate required for cycloaddition studies. Hydrogenation of 3-methoxyestra-1,3,5( 10),8, 14-pentaen-17β-yl acetate afforded 3-methoxy-8α-estra-1,3 ,5(10)-trien-17β-yl acetate, which was converted into 3-methoxy-8α-estra-1,3 ,5(10), 14, 16-pentaen-17-yl acetate. Cycloaddition with phenyl vinyl sulfone gave a mixture of products, which was converted into the desired 14,17α-ethano-8α-estra- 1,3,5(10)-triene-3, 17β-diol, by a hydrogenation, desulfonylation, deprotection reaction sequence. The unexpectedly complex result for the cycloaddition reaction was interpreted with the assistance of other cycloaddition reactions of the Δ¹⁴,¹⁶-dienyl acetate. 17,17-Ethylenedioxy-3-methoxy-9β-estra-l ,3,5(10)-trien-11-one was readily prepared from estrone using conventional methodology. Deoxygenation followed by standard functional group manipulation afforded 3-methoxy-9β-estra-1 ,3 ,5(10)-trien-17-one. As a result of the poor overall yield, the optimisation of a number of steps in this reaction sequence was investigated. Despite some improvement in the yields, subsequent conversion into the target, 14, 17a-ethano-9β-estra-1,3 ,5(10)-triene-3, 17β-diol was not synthetically useful. However, dehydrogenation of 14, 17α-ethanoestra-1,3,5(10)-triene-3, 17β-diol followed by standard functional group modification gave 14, 17 a-ethanoestra-1,3 ,5(10),9(11)-tetraene- 3, 17β-diyl diacetate, hydrogenation of which afforded 14, 17α-ethano-9β-estra-1 ,3,5(10)triene-3, 17β-diol, after conventional deprotection, in moderate yield.